Analysis of the Distribution of Volcanic Ash from the Eruption of Mount Kelud Based on Wind (Case Study of the Eruption Mount Kelud on 13 February 2014) - Imani, Romadhon Ilham; Sukarasa, I Ketut; Sumaja, Kadek; Suarbawa, Komang Ngurah; Paramartha, Ida Bagus Alit; Sutapa, Ngurah (BULETIN FISIKA; Vol 24 No 2 (2023): BULETIN FISIKA August Edition, 2023)
The distribution of volcanic ash from the eruption of Mount Kelud on 13 February 2014 had a significant impact on atmospheric conditions in the Java Island region. This research was conducted to identify the trajectory of volcanic dust, the mass value of the particles, and the range of distribution in the atmosphere which is affected by wind conditions. The influence of the wind is based on wind direction and speed by doing wind streamline modelling. Furthermore, the assistance of volcanic ash distribution was carried out using the Red, Green, Blue (RGB) composite image method, and the particle mass and distribution range of volcanic dust was carried out using hysplit modelling. The atmospheric layer analysed at the flight level area at 16 altitudes, namely at an altitude of 1.5-16.1 km. From the results of the analysis, it was found that the maximum wind speed is 38 m/s, which is at an altitude of 16.1 km. The trajectory of the distribution of volcanic ash heads to the Northeast and then most of it turns to the Southwest due to wind direction and speed. The highest maximum particle mass value is at an altitude of 16.1 km, which is 580,000 mg/m 2 with a particle distribution range of 2,600 km from the position of Mount Kelud .